Presumed Bartonella-Associated Spondylodiscitis in a 3-Year-Old Child: A Case Report and Review of the Literature - Hadi El Assaad; Eckehard Schumann; Christian Klemann; Nadine Dietze-Jergus; Christoph-Eckhard Heyde; Philipp Pieroh (Children)
With an incidence of 0.3 per 100,000, spondylodiscitis is a rare condition in children. It is typically bacterial in origin and most commonly caused by Staphylococcus aureus. Bone involvement in cat-scratch disease (CSD) due to Bartonella henselae is exceedingly rare, occurring in only 0.17–0.27% of cases. We present the case of a 3-year-old boy with a two-week history of intermittent back pain and a recent onset fever. Initial laboratory findings were unremarkable, and MRI revealed spondylodiscitis at L3/4 without abscess formation. Empirical antibiotic treatment with ampicillin/sulbactam showed no clinical response. Serologic testing revealed a positive Bartonella henselae IgM (IgG negative), leading to a change in antibiotic treatment to azithromycin and rifampicin for three weeks, resulting in rapid clinical improvement. Follow-up at nine weeks showed marked clinical and radiologic improvement. Although IgM subsequently turned negative without IgG seroconversion—a pattern previously described in Bartonella infections—this does not exclude the diagnosis. Biopsy or tissue PCR was not performed due to the mild clinical course. A review of the literature identified 28 pediatric cases of Bartonella henselae spondylodiscitis, with significant variation in diagnostic and treatment approaches. This case underscores the importance of considering Bartonella in the differential diagnosis of pediatric vertebral osteomyelitis.